Serum Levels of IL-6 Type Cytokines and Soluble IL-6 Receptors in Active B-Cell Chronic Lymphocytic Leukemia and in Cladribine Induced Remission - T. Robak; A. Wierzbowska; M. Blasinska-Morawiec; A. Korycka; J. Z. Blonski (Hindawi Limited, 1999)
We have investigated the serum concentrations of interleukin-6 (IL-6) and two IL-6 family cytokines-oncostatin M (OSM) and leukemia inhibitory factor (LIF)-in 63 patients with B-cell chronic lymphocytic leukemia (B-CLL) and 17 healthy controls using the enzyme-linked immunosorbent assay (ELISA) method. Simultaneously, we measured the serum levels of the soluble forms of two subunits of the IL-6 receptor complex-ligand binding glycoprotein 80 (sIL-6R) and glycoprotein 130 (sgp130). The cytokines and receptors were evaluated in 25 untreated patients and 38 patients treated with cladribine (2-CdA), as well as in 17 healthy controls. We have correlated the serum levels of these proteins with Rai's clinical stage of the disease, the response to 2-CdA treatment and some hematological parameters. We have also evaluated the correlation of the IL-6 serum level with the concentration of OSM and IL-6 soluble receptors. IL-6 was measurable in 62/63 (98.4%), OSM in 20/25 (80%) of untreated and 14/38 (37.8%) of the treated patients. sIL-6R and sgp130 were detectable in all 63 patients and LIF in none of the CLL patients. IL-6 serum level in untreated patients was not significantly different as compared to its concentration in the control group (P>0.05). However, in the patients treated with 2-CdA the IL-6 level was significantly lower (P<0.02), and the lowest concentration was found in the patients with complete remission (CR; median 1.4 pg/ml; P<0.02). The concentration of sIL-6R was significantly higher in untreated (median 61.8 ng/ml) and treated (median 50.1 ng/ml) CLL patients when compared to normal persons (median 41.2 ng/ml; P=0.04; P<0.001, respectively). There was no difference between the sIL-6R levels in the patients with CR and the healthy controls. In non-responders sIL-6R concentration was the highest and similar to its level in the untreated patients. OSM level was higher in the untreated patients (median 1.8 pg/ml) than in the normal controls (median 0.0 pg/ml; P<0.001) and in the CR patients (median 0.0 pg/ml; P<0.03). The serum concentration of sgp130 was similar in the untreated (median 480 pg/ml) and treated (median 470 pg/ml) patients, as well as in the healthy persons (median 420 pg/ml; P>0.05). We have found significant positive correlation between the levels of sIL6R and the lymphocytes count in CLL patients (Ρ=0.423; P<0.001). In addition, sIL-6R and OSM serum concentrations correlated also with CLL Rai stage. In conclusion, the serum level of IL-6, OSM and sIL-6R, but not LIF and sgp130, are useful indicators of CLL activity.